2017
DOI: 10.1021/acs.iecr.7b00380
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Optimization of Complex Distillation Systems with a New Pseudo-transient Continuation Model

Abstract: Complex distillation systems, such as extractive distillation systems and thermally coupled distillation systems have important applications in chemical industry. However, simultaneous optimization of all the variables in these systems with the rigorous MESH model is still difficult because of both the convergence problem and integer optimization problem. In this work, based on the pseudo-transient continuation (PTC) approach, a simple and robust PTC distillation model was developed in the equation-oriented (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 25 publications
1
54
0
Order By: Relevance
“…It is also observed that the purity of the recycle entrainer in the optimal design of the conventional ED is 0.9986 which is different from that of 0.9999 determined using heuristics in the work of Luyben [28]. This result is consistent with the result from Ma et al [17] for separation of the benzene/cyclohexane/ toluene mixture, where the recycle entrainer purity was only 0.85.…”
Section: Case Study 1: Acetone/chloroform Separationsupporting
confidence: 80%
See 3 more Smart Citations
“…It is also observed that the purity of the recycle entrainer in the optimal design of the conventional ED is 0.9986 which is different from that of 0.9999 determined using heuristics in the work of Luyben [28]. This result is consistent with the result from Ma et al [17] for separation of the benzene/cyclohexane/ toluene mixture, where the recycle entrainer purity was only 0.85.…”
Section: Case Study 1: Acetone/chloroform Separationsupporting
confidence: 80%
“…These fractional bypass efficiencies can be rounded to be 0 or 1 and a new optimal solution can be generated. It is demonstrated that the optimal solution does not change noticeably after the fractional bypass efficiencies round off in case studies of this work and the existing efforts [17,18].…”
Section: Modelling Of Edwcmentioning
confidence: 74%
See 2 more Smart Citations
“…Moreover, if gotten, the integer solutions on stage numbers correspond to poor local optima in some cases. 15,18 Consequently, the bypass efficiency model may lead in some cases to either poor local optimal solutions 18 or fractional bypass efficiencies. And thus, multitrials starting from different starting points are needed in pursuing a global optimum with integer stage numbers.…”
Section: Introductionmentioning
confidence: 99%